The Clinical Aspects and Prognostic Factors Concerning Survival in Patients With Recurrent Cervical Cancer After Radical Hysterectomy and Adjuvant Chemoradiotherapy - Zhu, Hui-Ting; Yan, Wen-Juan; Gao, Yu-Hua (Frontiers in Oncology, 2022)
Purpose To investigate the recurrence patterns and prognostic factors of patients with recurrent cervical cancer after radical hysterectomy with node dissection (RHND) followed by adjuvant radiotherapy (RT)/concurrent chemoradiotherapy (CCRT). Methods The medical records of 153 patients with pre-operative International Federation of Gynecology and Obstetrics stage IB-IIA cervical cancer, who were treated with RHND followed by adjuvant RT/CCRT at the Liaoning Cancer Hospital between January 1, 2012 and May 31, 2018, were retrospectively analyzed. Results The median disease progression-free survival time was 16 months, and 75.2% (115/153) of patients had a relapse within two years. The survival of patients with multi-site relapse was significantly lower in comparison to those with relapse in a single site (p < 0.001). The survival rate of patients with distant metastasis (DM) and combined recurrence (DM with localregional recurrence [LR]) was significantly lower than that of patients with only LR (p = 0.006, p < 0.001). Furthermore, the survival rate of patients with combined recurrence was significantly lower than that of patients with only DM (p = 0.046). Multivariate analysis showed that resection margin involvement, para-aortic and common iliac lymph node metastasis, DM, no treatment after disease relapse, and early disease relapse were independent prognostic factors associated with poor survival. Conclusion Most of the cervical cancer patients who received initial RHND followed by adjuvant RT/CCRT had a relapse within two years. Resection margin involvement, para-aortic and common iliac lymph node metastasis, DM, no treatment after recurrence, and early disease relapse were found to be prognostic factors in patients with recurrent cervical cancer after RHND followed by adjuvant RT/CCRT.